G-quadruplex-forming aptamer enhances the peroxidase activity of myoglobin against luminol. Issue 11 (7th June 2021) - Tsukakoshi, Kaori; Yamagishi, Yasuko; Kanazashi, Mana; Nakama, Kenta; Oshikawa, Daiki; Savory, Nasa; Matsugami, Akimasa; Hayashi, Fumiaki; Lee, Jinhee; Saito, Taiki; Sode, Koji; Khunathai, Kanjana; et al.
Abstract: Aptamers can control the biological functions of enzymes, thereby facilitating the development of novel biosensors. While aptamers that inhibit catalytic reactions of enzymes were found and used as signal transducers to sense target molecules in biosensors, no aptamers that amplify enzymatic activity have been identified. In this study, we report G-quadruplex (G4)-forming DNA aptamers that upregulate the peroxidase activity in myoglobin specifically for luminol. Using in vitro selection, one G4-forming aptamer that enhanced chemiluminescence from luminol by myoglobin's peroxidase activity was discovered. Through our strategy— in silico maturation, which is a genetic algorithm-aided sequence manipulation method, the enhancing activity of the aptamer was improved by introducing mutations to the aptamer sequences. The best aptamer conserved the parallel G4 property with over 300-times higher luminol chemiluminescence from peroxidase activity more than myoglobin alone at an optimal pH of 5.0. Furthermore, using hemin and hemin-binding aptamers, we demonstrated that the binding property of the G4 aptamers to heme in myoglobin might be necessary to exert the enhancing effect. Structure determination for one of the aptamers revealed a parallel-type G4 structure with propeller-like loops, which might be useful for a rational design of aptasensors utilizing the G4 aptamer-myoglobin pair.